INCLUSIVE EDUCATION STRATEGIES IN IMPROVING ACCESS AND QUALITY OF LEARNING FOR STUDENTS WITH SPECIAL NEEDS - Yasozanolo Halawa; Herlina Salmi; Zetmin (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
This study aims to examine inclusive education strategies that can improve access and quality of learning for students with special needs. Using the literature research method, this study analyzed a number of relevant journal articles, textbooks and policy documents to identify key principles, strategies and challenges in implementing inclusive education. Through thematic analysis, the study found that inclusive education requires a holistic approach that includes continuous teacher training, curriculum adaptation, integration of assistive technology and the application of differentiated and collaborative learning methods. The results show that the effectiveness of inclusive education depends on schools' readiness to adopt changes in policies and practices and their ability to provide adequate resources. The main challenges identified include limited resources, lack of specialized training for teachers and resistance to changes in teaching practices. Nonetheless, successful inclusive education strategies highlight the importance of collaboration between teachers, parents and students and the importance of continuous program evaluation and adjustment to meet the needs of students with special needs.